Citizen Justice : The Environmental Legacy of William O. Douglas-Public Advocate and Conservation Champion - McKeown, M. Margaret (Mary Margaret), 1951- (Book collections on Project MUSE., 2022)
"Citizen Justice: The Environmental Legacy of William O. Douglas-Public Advocate and Conservation Champion highlights William O. Douglas's dual role in fulfilling his constitutional duty as justice while catering to his personal commitment to serve the public as a citizen advocate"--